Prevalence of deciduous tooth erosion in childhood - Moimaz, Sas [UNESP]; Araújo, Pc [UNESP]; Chiba, Fy [UNESP]; Garbín, Cas [UNESP]; Saliba, Na [UNESP] (Wiley, 2013)
Objectives: The objective of this study was to estimate the prevalence of deciduous tooth erosion and to identify possible associations with sex, age and toothbrushing frequency in children aged 4-6 years. Methods: The sample was drawn from attendants (n = 7058) of 57 public preschools in a Brazilian city. Tooth wear index was used to evaluate erosion. Descriptive statistical analysis consisted of the calculation of the prevalence of dental erosion; chi-squared and Fisher's exact tests were performed to verify the association between dental erosion and sex, age and toothbrushing frequency. Results: Two thousand and seven hundred and fifty-nine preschool students were examined. Deciduous tooth erosion was observed in 0.6% of children and its incidence did not differ between sexes. The highest prevalence was observed in children aged 6 years (58.3%) and the most affected sextants were the fourth (22.86%) and sixth (20.00%), indicating that lingual and occlusal tooth surfaces were most frequently involved. The degree of involvement was classified as incipient in 54.29% of children and moderate in 45.71%. The significance level was set at 5%. No association was found between erosion and sex, age or toothbrushing frequency. Conclusions: The prevalence of deciduous tooth erosion was low in Brazilian children, and this disorder is not considered a public health problem in this part of the population. © 2013 John Wiley & Sons A/S.
Keywords: Child; Dental erosion; Health survey; Oral health